The Influence of Sharia Corporate Governance on Financial Performance of Islamic Commercial Banks in Indonesia - Melida Sari; Isni Andriana; Muizzuddin (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze and test the influence of Sharia Corporate Governance (SCG) on the financial performance of Islamic commercial banks in Indonesia during the 2020-2024 period. The SCG principles in this study consist of transparency, accountability, responsibility, independence, fairness, and the role of the Sharia Supervisory Board (SSB). This study uses a quantitative method with a content analysis approach to the annual reports of Islamic commercial banks registered with the Financial Services Authority (OJK). The study population includes all Islamic commercial banks in Indonesia, with a purposive sampling technique, resulting in 13 Islamic banks as observation samples. Data were analyzed using multiple linear regression to test the influence of each SCG variable on financial performance, proxied by Return on Assets (ROA). The results showed that the SCG variables simultaneously had a significant effect on the financial performance of Islamic commercial banks. Partially, the SCG variables proxied by transparency, accountability, independence, and fairness had a significant effect on financial performance, while the SCG variables proxied by responsibility and SSB did not have a significant effect on financial performance. These results indicate that the effective implementation of SCG principles is able to increase legitimacy and public trust, which ultimately has an impact on improving the financial performance of Islamic commercial banks in Indonesia